Dietary education provision within a cardiac rehabilitation programme in the UK: a pilot study. (2nd August 2020) - Moore, Chelsea E; Tsakirides, Costas; Rutherford, Zoe; Swainson, Michelle G; Birch, Karen M; Ibeggazene, Said; Ispoglou, Theocharis
Abstract : Background/aims: The primary aim of this study was to evaluate the effectiveness of two 30-minute dietary education sessions, within cardiac rehabilitation, as a means to optimise nutrient and energy intakes. A secondary aim was to evaluate patients' habitual physical activity levels. Methods: Thirty patients (males: n =24, 61.8±11.2 years; females: n =6, 66.7±8.5 years) attended a 6-week early outpatient cardiac rehabilitation programme in the UK and received two 30-minute dietary education sessions emphasising Mediterranean diet principles. Energy intakes and nutrient intakes were measured through completion of 3-day food diaries in weeks one and six (before and after the dietary education sessions) to assess the impact of these sessions on nutrient intakes. At the same time-points, a sub-group ( n =13) of patients had their physical activity levels assessed via accelerometery to assess the impact of the cardiac rehabilitation programme on physical activity. Results: Estimated energy requirements at week one (1988±366 kcal d −1 ) were not matched by actual energy intakes (1785±561 kcal d −1 ) ( P =0.047, d =−0.36). Energy intakes reduced to 1655±470 kcal d −1 at week six ( P =0.66, d =−0.33) whereas estimated energy requirements increased as a function of increased activity (cardiac rehabilitation sessions). Nutrient intakes remained suboptimal, while no significant increases were observed in healthy fats and fibre, which are core elements of a Mediterranean diet. Statistically significant increases were not observed in physical activity; however, patients decreased sedentary time by 11±12% in week six compared with week one ( P =0.009; d =−0.54). Conclusions: The present study findings suggest that two 30-minute dietary education sessions did not positively influence energy intakes and nutrient intakes, while habitual physical activity levels were not significantly increased as a result of the cardiac rehabilitation programme. Future research should explore means of optimising nutrition and habitual physical activity within UK cardiac rehabilitation.